2019
DOI: 10.1111/bjet.12883
|View full text |Cite
|
Sign up to set email alerts
|

Are quiz‐games an effective revision tool in Anatomical Sciences for Higher Education and what do students think of them?

Abstract: Recently, there has been an increased volume of pedagogical research and practice of mobile learning (m-learning) and gameplay in education. This paper presents the findings of a study that examined the effect on achievement and explored student perception towards quiz-game play prior to an anatomy assessment in first year Higher Education students. Achievement data was collected over two academic years at all module assessment (A1-A4) points. A1 was used as a baseline, showing no difference between groups or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…In 10 (3%) of the studies included in the research, they compared the traditional learning method and mobile application methods to investigate the effect of mobile learning. In 8 (26%) of the studies, it was observed that the final exam results of the students who learned anatomy with the mobile application were higher than the students who learned with the traditional method (Chakraborty & Cooperstein, 2018;Fernández-Alemán, López-González, et al, 2016;Fernández-Alemán, Lopez-Gonzalez, et al, 2016;Lazarus et al, 2017;Moro et al, 2017;Traser et al, 2015;Wilkinson & Barter, 2016;Wilkinson et al, 2020). In the other 2 (6%) studies, it was observed that the anatomy final exam results of the experimental groups were higher, but there was a decrease in their cognitive levels (Bork et al, 2021;Küçük et al, 2016).…”
Section: Surveymentioning
confidence: 99%
See 3 more Smart Citations
“…In 10 (3%) of the studies included in the research, they compared the traditional learning method and mobile application methods to investigate the effect of mobile learning. In 8 (26%) of the studies, it was observed that the final exam results of the students who learned anatomy with the mobile application were higher than the students who learned with the traditional method (Chakraborty & Cooperstein, 2018;Fernández-Alemán, López-González, et al, 2016;Fernández-Alemán, Lopez-Gonzalez, et al, 2016;Lazarus et al, 2017;Moro et al, 2017;Traser et al, 2015;Wilkinson & Barter, 2016;Wilkinson et al, 2020). In the other 2 (6%) studies, it was observed that the anatomy final exam results of the experimental groups were higher, but there was a decrease in their cognitive levels (Bork et al, 2021;Küçük et al, 2016).…”
Section: Surveymentioning
confidence: 99%
“…Within the scope of the systematic review, it was stated in 20 (66%) studies that mobile learning facilitates three-dimensional learning, is motivating and fun. They stated that they can access anatomy notes and images at any time of the day (Bolatli & Kizil, 2022;Bork et al, 2021;Fernández-Alemán, López-González, et al, 2016;Gnanasegaram, Leung, & Beyea, 2020;Golenhofen et al, 2020;Havens, Saulovich, & Saric, 2020;Jamali, Shiratuddin, Wong, Oskam, & Sciences, 2015;Kurniawan & Witjaksono, 2018;Küçük, Kapakin, & Göktaş, 2016;Lazarus, Sookrajh, & Satyapal, 2017;Mendez-Lopez et al, 2022;Mogali et al, 2019;Moro, Štromberga, Raikos, & Stirling, 2017;Morris, Lambe, Ciccone, & Swinnerton, 2016;Pickering, 2015;Stewart & Choudhury, 2015;Stirling & Birt, 2014;Traser, Hoffman, Seifert, & Wilson, 2015;Wilkinson & Barter, 2016;Wilkinson et al, 2020). In 19 (63%) studies, the learning effectiveness of medical school students in anatomy education with mobile applications was investigated, and positive feedback was received from the students.…”
Section: The Effect Of Anatomy Learning With a Mobile Application On ...mentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, computer based learning methods show no overt effect when compared to traditional study methods [23]. Moreover, the factor of luck in MCQ is a known design problem and when not enough care is taken to actively discourage the random guessing, exams become unreliable [24][25][26][27][28][29]. CBM was designed to tackle the issues presented above-identifying students' conceptual misunderstandings, identifying students' areas for improvement and actively discouraging random guessing [30][31][32].…”
Section: Introductionmentioning
confidence: 99%